2022
DOI: 10.3389/fvets.2022.938826
|View full text |Cite
|
Sign up to set email alerts
|

Transport Stress Induced Cardiac NO-NOS Disorder Is Mitigated by Activating Nrf2/HO-1/NQO1 Antioxidant Defense Response in Newly Hatched Chicks

Abstract: With the development of the intensive poultry industry, the health problems of chickens caused by transportation have attracted more and more attention. Transport stress reduces performance, immune function, and meat quality in chicks, which has become one of the most important factors that endanger the development of the poultry industry. Currently, studies on the effects of transport stress have mainly focused on the performance of livestock and poultry to be slaughtered. However, the effects of transport st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Damaged mature cardiomyocytes, as the postmitotic cells, are unable to self-recover, which means that cardiac tissue is irreversible. Moreover, according to previous studies, TS can cause heart damage in chicks, as evidenced by the obvious vacuolar degeneration and necrosis of cardiomyocytes after TS lasting 8 h ( Sun et al, 2018 ; Xu et al, 2022 ). However, how TS induces cardiac injury in chicks is not yet fully understood.…”
Section: Introductionmentioning
confidence: 65%
See 3 more Smart Citations
“…Damaged mature cardiomyocytes, as the postmitotic cells, are unable to self-recover, which means that cardiac tissue is irreversible. Moreover, according to previous studies, TS can cause heart damage in chicks, as evidenced by the obvious vacuolar degeneration and necrosis of cardiomyocytes after TS lasting 8 h ( Sun et al, 2018 ; Xu et al, 2022 ). However, how TS induces cardiac injury in chicks is not yet fully understood.…”
Section: Introductionmentioning
confidence: 65%
“…It has been well documented that TS can cause weight loss, immune disorders, and metabolic dysfunction in animals ( Li et al, 2017 ). Of note, chicks often experience a higher heart rate or even sudden death during or after transportation, which is considered to be related to heart damage caused by TS ( Li et al, 2017 ; Chen et al, 2022a ; Xu et al, 2022 ). A previous study in chicks indicated that TS evoked cardiac damage and notably reduced body weight via inducing nitric oxide and arresting the heat shock response ( Li et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Heat stress has been shown to cause morphological damage to the lungs, trachea and bronchi, and oxidative stress after a certain length of transportation has been shown to trigger signi cant changes in the expression of apoptosis-related genes Bcl-2 and Bax, as well as autophagy-related genes LC3B, PINK1 and Parkin [ 7,26]. Similarly, during transportation, animals are subjected to counter-organismic disturbances such as environmentally harmful chemicals, bumps and occlusions, and temperature and humidity discomfort, which can trigger a series of events at the cellular and molecular level, such as the elicitation of malondialdehyde (MDA), reactive oxygen species (ROS), nitric oxide, DNA/RNA oxidative stress damage products (DNA/RNA OSDP), and heat shock proteins 27, 70, 90 ( HPS27, 70, 90) and other indicators of oxidative stress and heat stress climbed, which ultimately induced in ammation, apoptosis and autophagy in goats after causing them to be subjected to oxidative stress and heat stress [27][28][29][30]. The lungs are the gateway for gas exchange, and their normal activity and linkage to the immune system facilitates the repair of infections and damage caused by transportation stress [31].…”
Section: Discussionmentioning
confidence: 99%